2004
DOI: 10.1074/jbc.m407161200
|View full text |Cite
|
Sign up to set email alerts
|

L-ficolin Is a Pattern Recognition Molecule Specific for Acetyl Groups

Abstract: L-ficolin and H-ficolin are molecules of the innate immune system. Upon recognition of a suitable target they activate the complement system. The ligand recognition structure of ficolins is contained within a fibrinogen-like domain. We examined the selectivity of the ficolins through inhibiting the binding to bacteria or to beads coupled with N-acetylglucosamine. The binding of L-ficolin to Streptococcus pneumoniae 11F and the beads was inhibited by N-acetylated sugars and not by non-acetylated sugars. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
154
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(174 citation statements)
references
References 41 publications
(32 reference statements)
10
154
2
2
Order By: Relevance
“…Instead, recognition of these molecules appears to involve minimal structural requirement for the acetyl group, and virtually no requirement for the remainder of the molecule. Although this type of recognition was somewhat unexpected, it is fully consistent with the observed ability of a wide range of small acetylated compounds to partially inhibit the binding of L-ficolin to GlcNAc-Sepharose beads and to Streptococcus pneumoniae (Krarup et al, 2004).…”
Section: Structural Determinants For the Sensing Properties Of Human supporting
confidence: 78%
“…Instead, recognition of these molecules appears to involve minimal structural requirement for the acetyl group, and virtually no requirement for the remainder of the molecule. Although this type of recognition was somewhat unexpected, it is fully consistent with the observed ability of a wide range of small acetylated compounds to partially inhibit the binding of L-ficolin to GlcNAc-Sepharose beads and to Streptococcus pneumoniae (Krarup et al, 2004).…”
Section: Structural Determinants For the Sensing Properties Of Human supporting
confidence: 78%
“…L-ficolin binds to GlcNAc residue next to galactose at the nonreducing terminal of the oligosaccharide (21). Several reports recently showed that L-ficolin could bind to various acetylated compounds, 1,3-ÎČ-D glucan, a molecular marker of yeast and fungal cell walls, lipopolysaccharide (LPS) on gram-negative bacterial species and Lipoteichoic Acid (LTA) on the gram-positive bacteria Staphylococcus aureus and Streplococcus pneumoniae, following the activation of complement (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…H-ficolin (synonymous with ficolin-3 or Hakata-antigen) has a primary sequence that is 48% identical to that of L-ficolin and binds to GlcNAc, and D-fucose (14). The GlcNAc binding activity of H-ficolin, unlike that of L-ficolin, is not inhibited by acetyl compounds (31). M-ficolin (synonymous with ficolin-1 or Ficolin/ P35-related protein) has a primary sequence that is 80 and 48% identical to those of L-ficolin and H-ficolin, respectively (14,28).…”
mentioning
confidence: 99%
“…Lficolin (synonymous with ficolin-2 or Ficolin/P35) binds to GlcNAc (29,30) and GalNAc (8). The binding ability is inhibited by acetylated compounds, indicating that this protein specifically recognizes acetyl groups (31). L-ficolin activates the lectin complement pathway upon binding to lipoteichoic acid, a cell wall component of all Gram-positive bacteria (32).…”
mentioning
confidence: 99%